Dynamics in Inter-Firm Collaboration: The Impact of Alliance Capabilities on Performance - Gerrit Willem Ziggers; Brian Tjemkes (International Journal on Food System Dynamics, 2010)
In this study we question the direct relationship between a firm’s alliance capability and alliance performance. We contend that this relationship is mediated through post-information factors such as alliance management and relational quality. Drawing from the Resource Based View a model is presented that explicates these indirect relationships. Partial least squares analysis was used to test three hypotheses, using a sample of Dutch alliance managers responsible for non‐equity alliances in agribusiness and the food industry. Our empirical findings affirm the hypothesized indirect relationships between a firm’s alliance capability and alliance performance.